DNA Diagnostics of Hereditary Hearing Loss: A Targeted Resequencing Approach Combined with a Mutation Classification System. Issue 8 (6th May 2016) - Sommen, Manou; Schrauwen, Isabelle; Vandeweyer, Geert; Boeckx, Nele; Corneveaux, Jason J.; van den Ende, Jenneke; Boudewyns, An; De Leenheer, Els; Janssens, Sandra; Claes, Kathleen; Verstreken, Margriet; Strenzke, Nicola; et al.
Abstract : In this study, a targeted resequencing panel for hearing loss was developed including 79 hearing loss genes. One hundred thirty one presumed autosomal‐recessive non‐syndromic hearing loss patients were analyzed for SNVs, Indels, and CNVs. We estimate that combining prescreening of GJB2 with our panel leads to a definite diagnosis in 26%–31% and a probable diagnosis in 12% of patients. ABSTRACT: Although there are nearly 100 different causative genes identified for nonsyndromic hearing loss (NSHL), Sanger sequencing‐based DNA diagnostics usually only analyses three, namely, GJB2, SLC26A4, and OTOF . As this is seen as inadequate, there is a need for high‐throughput diagnostic methods to detect disease‐causing variations, including single‐nucleotide variations (SNVs), insertions/deletions (Indels), and copy‐number variations (CNVs). In this study, a targeted resequencing panel for hearing loss was developed including 79 genes for NSHL and selected forms of syndromic hearing loss. One‐hundred thirty one presumed autosomal‐recessive NSHL (arNSHL) patients of Western‐European ethnicity were analyzed for SNVs, Indels, and CNVs. In addition, we established a straightforward variant classification system to deal with the large number of variants encountered. We estimate that combining prescreening of GJB2 with our panel leads to a diagnosis in 25%–30% of patients. Our data show that after GJB2, the most commonly mutated genes in a Western‐European population are TMC1, MYO15A, and MYO7A (3.1%). CNV analysis resulted in the identification of causative variants in two patients in OTOA and STRC . One of the major challenges for diagnostic gene panels is assigning pathogenicity for variants. A collaborative database collecting all identified variants from multiple centers could be a valuable resource for hearing loss diagnostics.